Instability evolution in the hypersonic boundary layer over a wavy wall. (25th July 2022) - Zhu, W.K.; Gu, D.W.; Si, W.F.; Zhang, M.J.; Chen, S.Y.; Smith, C.R.; Zhu, Y.D.; Lee, C.B.
Abstract: Abstract : The effects of a wavy wall on the stability of a hypersonic boundary layer on a flared cone are investigated by detailed experimental measurements and direct numerical simulations. The non-contact optical measurement method of focused laser differential interferometry is used to measure the disturbance development within the wavy region. The measurement results show that the second mode for the wavy wall is suppressed significantly compared with the smooth wall, and that multiple disturbances at low frequencies appear within the wavy region. Numerical corroboration against experimental measurements reveals good quantitative agreement. It is found that the disturbances at $f=360$  kHz on the wavy wall are suppressed appreciably, which are very significant on the smooth wall. And the disturbances at $f=140$  kHz and $f=260$  kHz develop within the wavy region, and increase considerably. Also, the disturbances achieve a significant increase over the first half of a wavy trough and become more stable over the second half of a wavy trough. The physical mechanism is found to be due to the change in wall geometry and is attributed to the spatially modulated mean flow. The disturbance growth rate is closely related to the level of the mean-flow distortion.